LEARNING COMMUNITIES IN THE U. S. HIGHER EDUCATION - Sharanova, Yuliia (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article highlights the features of the learning communities in the educational practice of higher education institutions in the United States of America. The learning community is characterized as a form of long-term group cooperation in the U. S. higher education institutions, which provides a favorable educational environment where each student is individually responsible not only for their own educational activities, but also the education of other students and encourages them to actively interact, gives support, assistance in performing educational tasks. It is noted that the learning communities in the U. S. higher education institutions rely on active teaching methods, cooperation and interdisciplinarity, creating favorable conditions for the socialization of students. The learning communities under study provide a sense of group identity, cohesion and uniqueness for all students; encourage continuity and integration of various types of experience (academic, life and in some way professional experience and experience of performing socially significant activities). It was found that joint educational and cognitive activities, and interaction in learning communities encourage students to identify and enhance their communication skills, critical thinking skills, cooperation, be open and tolerant, build stronger relationships with each other and with professors, as well as more actively interact with the content of academic disciplines they study on the interdisciplinary basis. The typical structure of learning communities of students is outlined, who actively interact under the guidance of two or three professors from different disciplines in order to solve the tasks both during classes and in the process of extracurricular activities. The two main types of learning communities in the activities of higher education institutions in the United States are considered, among which are learning communities of thematic and professional orientation.